2013
DOI: 10.1002/pc.22423
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of in situ prepared nanocomposites of PS and TIO2 nanoparticles surface modified with alkyl gallates: Effect of alkyl chain length

Abstract: Incorporation of surface modified TiO2 nanoparticles into polystyrene (PS) matrix was achieved by in situ bulk radical polymerization of styrene. The surface of TiO2 nanoparticles was modified with four amphiphilic esters of the gallic acid (octyl, decyl, lauryl and cetyl gallate), which have different lengths of hydrophobic alkyl chain (C8–C16). FTIR and UV‐Vis spectroscopy measurements confirmed the formation of a charge transfer complex between surface Ti atoms and gallic esters. Microstructural characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
3
23
0
1
Order By: Relevance
“…The absorption of the surface modified TiO 2 nanoparticles starts at around 650 nm and the absorption of aqueous TiO 2 starts at around 380 nm. This significant shift of the absorption spectra indicates the reaction of gallic acid esters with surface Ti atoms of nanoparticles and the formation of CTC [26,30]. However, the obtained results revealed that the hydrophobic part length of gallates used for the surface modification of TiO 2 nanoparticles had no significant influence on the position of the absorption spectra of TiO 2 nanoparticles.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The absorption of the surface modified TiO 2 nanoparticles starts at around 650 nm and the absorption of aqueous TiO 2 starts at around 380 nm. This significant shift of the absorption spectra indicates the reaction of gallic acid esters with surface Ti atoms of nanoparticles and the formation of CTC [26,30]. However, the obtained results revealed that the hydrophobic part length of gallates used for the surface modification of TiO 2 nanoparticles had no significant influence on the position of the absorption spectra of TiO 2 nanoparticles.…”
Section: Resultsmentioning
confidence: 84%
“…Aromatic ligands with two or three adjacent phenolic OH groups (catechol, pyrogallol and gallic acid) can be adsorbed on the surface of TiO 2 by forming chelating or bridging complexes with titanium ions on the surface [24][25]. In our previous works, TiO 2 nanoparticles were surface modified with different alkyl gallates [26] and then incorporated into the poly(methyl mehacrylate) and epoxy matrix [27]. The length of the aliphatic part of the used gallates showed a great effect on dispersability of the surface modified TiO 2 nanoparticles and on the properties of both matrices.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of inorganic oxide nanoparticles permits the adjustment of different characteristics of organic polymers, like thermal stability, optical, mechanical and/or electrical properties [5,9,10]. Composites containing TiO 2 nanoparticles dispersed in a polymeric matrix have a wide range of applications, i.e., food packaging materials with biocidal and photodegradability properties [11], the dielectric material of capacitors and thin films transistors [12,13], high refractive index coatings [10] and visible transparent UV-filters [14].…”
Section: Introductionmentioning
confidence: 99%
“…Both titanium and silicon dioxide nanosized particles have been widely used to extend the functional characteristics of polymer composites . For example, the embedding of titanium dioxide (TiO 2 ) nanoparticles into thermosetting polymers and elastomers results in enhancements in their thermal resistance, stiffness and toughness, thermal conductivity, tensile properties, impact strength, and fracture toughness . It is remarkable that the aforementioned improvements manifest themselves at low filler contents (≤5 wt %) and are related to the stabilization of the polymer's inner structure because of the binding of macromolecular chains to the superficial centers of the particles …”
Section: Introductionmentioning
confidence: 99%